2020
DOI: 10.3390/ma13030585
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ethylene–propylene Composites Filled with Perlite and Vermiculite Minerals: Mechanical, Barrier, and Flammability Properties

Abstract: Perlite and vermiculite are naturally occurring minerals, commonly used by industry to obtain highly thermoisolative and/or non-flammable materials. However, there has been little research into the preparation and application of rubber compounds containing these inexpensive mineral fillers. Here, we show the benefits of perlite and vermiculite minerals as fillers for ethylene-propylene rubber (EPM) composites. To obtain more uniform dispersion and improved compatibility between the minerals and the elastomer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
(46 reference statements)
1
21
0
Order By: Relevance
“…By increasing the filler loading, more bulky foam was obtained and the amount of residual char increased parallel with the TGA results. As reported in the literature, 22,28,67,7177 incorporation of VMT led to increase in the flame spread resistance and some important reasons were underlined as follows. As known, VMT is a natural mineral that mostly composed of SiO 2 , Al 2 O 3 , Fe 2 O 3 .…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…By increasing the filler loading, more bulky foam was obtained and the amount of residual char increased parallel with the TGA results. As reported in the literature, 22,28,67,7177 incorporation of VMT led to increase in the flame spread resistance and some important reasons were underlined as follows. As known, VMT is a natural mineral that mostly composed of SiO 2 , Al 2 O 3 , Fe 2 O 3 .…”
Section: Resultsmentioning
confidence: 77%
“…Removal of the char also made the sample vulnerable against flame. 71 While the residuals of the samples with vermiculite showed foamy morphology, SEBS showed a rigid solid morphology. By increasing the filler loading, more bulky foam was obtained and the amount of residual char increased parallel with the TGA results.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Most elastomers are unviable for industrial applications without any reinforcing filler, since they do not meet the technological requirements for, e.g., mechanical strength, abrasion resistance, damping performance, or hardness. Therefore, in the rubber industry, many types of fillers with different characteristics and activities are used [ 1 , 2 , 3 , 4 , 5 ]. The reinforcing effect of the filler mainly depends on the size of the particles and their distribution in the elastomer matrix, as well as on the specific surface area and chemical and physical nature of the filler [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maciejewska et al [29] reported that the application of different ILs in nitrile rubber composites can lead to significant improvements in the crosslink density of vulcanizates, due to the more uniform dispersion of the filler and other components in the curing system. We observed such effects in our previous studies of ILs in different elastomer systems [28,30,31]. In the present study, significantly higher values for the crosslink density were observed in the case of NBR/BMIMAlCl 4 (8.1•10 −5 mol/cm 3 for 2.5 phr and 10.2•10 −5 mol/cm 3 for 5 phr) compared to NBR/BMIMTFSI (6.9•10 −5 mol/cm 3 for 2.5 phr and 7.2•10 −5 mol/cm 3 for 5 phr).…”
Section: Rheometric Measurements Crosslink Density and Transparency Effectmentioning
confidence: 64%